Utilising uniportal video-assisted thoracoscopic surgery for pericardial window: A 12-year single-centre experience in the diagnosis and treatment of pericardial effusion - Agar, Mehmet; Gulcek, Ilham; Kalkan, Muhammed; Ulutas, Hakki; Celik, Muhammet Reha (Wolters Kluwer Medknow Publications, 2025)
Introduction:Uniportal video-assisted thoracoscopic surgery (Uni-VATS) is an effective minimally invasive technique for pericardial drainage, biopsy and window creation in cases of pericardial effusion (PE).Patients and Methods:This retrospective study evaluated 73 patients with PE who underwent pericardial window procedures between 2012 and 2024. Intraoperative and post-operative data related to Uni-VATS were assessed.Results:The mean age of the patients was 53.79 +/- 17.79 years (10-82 years), with 34 (46.6%) females and 39 (53.4%) males. The mean volume of pericardial fluid drained after window creation was 446.23 +/- 199.81 cc (75-1100 cc). The mean operation time was 42.87 +/- 12.79 min, and chest drain removal occurred after an average of 1.8 +/- 1.2 days. The mean duration until discharge or referral to the follow-up clinic was 5.98 +/- 2.14 days. In addition to the pericardial window procedure, pleural biopsy was performed in 12 patients, mediastinal mass biopsy in eight patients and wedge resection for parenchymal nodules in six patients. Microbiologic and virologic cultures of the fluids were negative in all cases. Among the 41 patients with benign cytology, pericardial biopsy results indicated tuberculosis in four patients (5.4%), amyloidosis in one patient (1.3%) and chronic or subacute nonspecific pericarditis in the remaining patients.Conclusion:Uni-VATS is a novel and safe technique that may be the preferred choice for pericardial window due to its diagnostic and therapeutic efficacy, ability to perform simultaneous procedures, favourable impact on operation duration/hospital stay, low complication rates and superiority compared to traditional methods.
Keywords: Pericardial effusion; pericardial window; thoracoscopic surgery; uniportal; video-assisted